STRUCTURE, BEHAVIOR, AND MARKET PERFORMANCE ON MARKETING OF PATCHIE OIL IN BUKUT VILLAGE, TERANGUN DISTRICT GAYO LUES DISTRICT - Authar ND, Muhammad; Puteh, Anwar; Alfiady, Teuku (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
Patchouli (Pogostemon cablin Benth) is an essential oil-producing plant which is a source of foreign exchange for the country. Indonesia is currently the world's producer of patchouli oil with a contribution of 90%, for that it is necessary to maintain market opportunities by increasing production through appropriate cultivation techniques, improving the quality of patchouli oil and developing patchouli plantings in areas that have bright prospects seen from the level of suitability. land and climate.The purpose of this study was to determine market structure, market behavior (various forms of collusion) and market appearances that occurred in the marketing of nimal oil in Bukut Village, Terangun District, Gayo Lues Regency. The data used are primary data and secondary data, for market participants, snowball sampling is used. The method used to analyze the market structure is Concentration Ratio analysis tools (Market Share, Herfindal Index and Concentration Ratio for Biggest Four or ), Degree of Product Differentiation, Barriers to Market Entry and Level of Market Knowledge. To analyze Market Behavior, it is descriptively analyzed about collusion and strategies that occur. To analyze the Market Performance used the analysis tools of Marketing Margin, Share Price, and Cost and Profit Ratio.〖CR〗_4.Market share at the collector levelthere is an oligopoly marketing system for patchouli oil with loose concentration. The concentration of buyers in marketing patchouli oil in Bukut village, both collectors, village collectors, and representative warehouses/ wholesalers is oligopsony. The marketing structure of Patchouli Oil in Gayo Lues, at the level of collector traders is a loose oligopoly with a CR4 value of 0.5421, at the level of a village collector it is a tight oligopoly with a CR4 value of 0.8855, while at the warehouse representative/ wholesaler level it is a tight oligopoly with a CR value, reaching 1.00. should have a value of 1.00 is a monopoly, but because there are still three competing companies, it is categorized as a strict oligopoly.